Challenges in the diagnosis and management of autoimmune hemolytic anemia: A case-based approach. Experience from a tertiary care hospital in the Haryana region - Geetika Sharma; Shilpi More; Saroj Rajput; Nimisha Sharma; Sonu Choudhary; Tathagata Chatterjee (Indian Journal of Pathology and Microbiology)
Background: Autoimmune hemolytic anemia (AIHA) is a rare immune disorder which occurs when antibodies are directed against self red blood cells (RBCs) leading to hemolysis. AIHA is widely classified as warm autoimmune hemolytic anemia, cold agglutinin syndrome, mixed AIHA, paroxysmal cold hemoglobinuria and rarely drug induced AIHA. The pathogenesis of AIHA is complex interplay between genetic predisposition, immune dysregulation and enviornmental triggers. A direct antiglobulin test can be used to assess the immunological origin of the hemolysis in order to diagnose AIHA after identifying laboratory and clinical symptoms of hemolysis. Objective: The objective is to understand underlying mechanism in AIHAs, and usage of targeted therapies to modulate specific components of the immune response. Materials and Methods: We are hereby presenting a case series of 11 clinically suspected cases of AIHA in collaboration with their clinical features, immuno-hematological and other laboratory parameters, Flow cytometric analysis of lymphocyte subset in relevant cases, underlying etiology as well as serological subtype are also included. Results: Majority of the patients were categorized as secondary AIHA (7/11, 63.63%). Out of 11 cases 7 were serologically subtyped as warm AIHA (7/11, 63.63%) ,2 cases were DaaT negative AIHA (2/11;18.18%), 2 cases were characterized as mixed AIHA subtype (2/11, 18.18%). Conclusion: Accurate subtyping of AIHA requires a systematic immunohematological approach coupled with comprehensive evaluations of clinical, hematological, and biochemical parameters.